Academic Stress and Happiness among Students: A Literatur Review - Fairuz Zanirah; Deasyanti; Dyah Ratna Suratri; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This literature review explores the dynamics of academic stress and happiness among students across various educational levels. Academic stress, arising from factors such as high expectations, heavy workloads, and peer pressure, negatively impacts students' well-being and happiness. Research indicates a consistent negative correlation between academic stress and happiness, emphasizing the urgent need for effective support systems within educational institutions. The review highlights key factors that influence this relationship, including emotional closeness with family, self-efficacy, and coping mechanisms such as mindfulness and physical activity. Additionally, the transition to online learning during the COVID-19 pandemic exacerbated academic stress and hindered happiness. The findings underscore the importance of creating supportive environments and collaborative efforts among educators, parents, and communities to enhance students' emotional and psychological well-being, enabling them to thrive academically and personally.